2021
DOI: 10.1186/s40816-021-00317-w
|View full text |Cite
|
Sign up to set email alerts
|

Sida acuta Burm.f. leaves ethanol extract ameliorates haematological and biochemical alterations induced by Plasmodium berghei ANKA-65 in mice

Abstract: Background Malaria has continued to be a threat to man and his wellbeing, especially Africans and Asians. New antimalarial drugs are urgently needed to mitigate malaria treatment failure due to resistant Plasmodium species. Medicinal plants used by indigenous Nigerians for treating fever and malaria such as Sida acuta Burm.f. (Malvaceae) could be a promising source of lead compounds for developing new generations of antimalarial drugs. The effects of ethanol extract of S. acuta leaves (EESAL) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
8
1
0
Order By: Relevance
“…The increased activities of the aminotransferases (AST, ALT) and alkaline phosphatase could be as a result of hepatocellular injury (Gowda et al, 2009) while the increased hyperbilirubinemia could be due to parenchymal liver cell damage and biliary obstruction induced by the liver schizonts of malaria parasite (Limdi and Hyde, 2003;Hoekstra et al, 2013). This finding is in agreement with previous studies (Enechi et al, 2021;Iyiola, 2020;Joshua et al, 2020) which reported increased liver enzyme activities and hyperbilirubinemia in mice infected with Plasmodium berghei. The reduction of the elevated AST, ALT and ALP showed that the extract was effective in reversing the hepatocellular damage caused by the Plasmodium parasite.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The increased activities of the aminotransferases (AST, ALT) and alkaline phosphatase could be as a result of hepatocellular injury (Gowda et al, 2009) while the increased hyperbilirubinemia could be due to parenchymal liver cell damage and biliary obstruction induced by the liver schizonts of malaria parasite (Limdi and Hyde, 2003;Hoekstra et al, 2013). This finding is in agreement with previous studies (Enechi et al, 2021;Iyiola, 2020;Joshua et al, 2020) which reported increased liver enzyme activities and hyperbilirubinemia in mice infected with Plasmodium berghei. The reduction of the elevated AST, ALT and ALP showed that the extract was effective in reversing the hepatocellular damage caused by the Plasmodium parasite.…”
Section: Discussionsupporting
confidence: 94%
“…However, the administration of the extract significantly (p < 0.05) increased the haemoglobin concentration in the test groups. This result is consistent with previous studies (Aragaw et al, 2020;Joshua et al, 2020;Enechi et al, 2021). The increased concentration of haemoglobin in the treated animals could possibly be as a result of the inhibition of the parasite's digestion of haemoglobin by the secondary metabolites present in the extract.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The administration of the extract, on the other hand, signi cantly (p < 0.05) raised the haemoglobin concentration in the test groups. This result is consistent with prevous studies (Aragaw et al, 2020;Joshua et al, 2020;Enechi et al, 2021). The activity of some of the secondary metabolites in the extract could be responsible for the observed higher haemoglobin concentration in the treated animals.…”
Section: Discussionsupporting
confidence: 92%
“…It has been used in Indian traditional medicine for several diseases such as kidney stone and urinary diseases treatment (diuretic) [ 9 , 10 ]. Moreover, the other previous report [ 13 ] of acute toxicity test showed that there was no death recorded in mice dosed with SAEE at 5000 mg/kg body weight. No significant changes were observed in body weight and behaviour within 24 h. Our previous study reported that SAAE contained the phenolic compounds (i.e., p-hydroxybenzoic acid, ferulic acid, and resveratrol) and showed antibacterial activity on several bacterial reference strains [ 11 ].…”
Section: Discussionmentioning
confidence: 74%